A Case Study of Choices of the Host University and Decisions to Stay or Leave the U.S. upon Graduation of Chinese Adult and Traditional Students - Xi Lin; Hong Shi; Mingyu Huang (Adult Education Research Conference, 2016)
Chinese students are the largest group among all the international students. Many factors motivate them to study in the U.S. and their decision to stay or leave the U.S. after graduation. However, limited research investigates these aspects by differentiating students into non-traditional students and traditional student groups. As a result, this study conducted individual interviews to examine: 1) factors that influence Chinese students’ (non-traditional students vs. traditional students) choices of the host college or university in the U.S.; and 2) their decisions to stay or leave the U.S. after graduation. Eleven Chinese students participated in this study, including seven female students and four male students. Their ages range from 23 to 30 years old with the mean of 25.8. They are from majors across STEM and non-STEM fields. Among them, four had working experience who are considered as non-traditional students, while the rest are traditional students. Findings show that Chinese non-traditional students consider financial aid availability most when choosing the college abroad, while traditional students focused on the ranks of academic programs or colleges. In addition, most Chinese non-traditional students preferred to return to their home country. However, most traditional students would choose to remain in the U.S. after graduation. Meanwhile, most students desired to have some working experience in the U.S. It is hoped that this study would lead to a greater awareness of Chinese international students and enlighten higher education professionals and administrators with practical ideas to build a better campus environment and climate to serve this growing population.
Keywords: Chinese students; non-traditional students; college choice; student mobility; higher education